1980
DOI: 10.1159/000250358
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Collagenous Plaque of the Hand (Linear Keratoelastoidosis of the Hands)

Abstract: Clinical and histological features of three examples of degenerative collagenous plaques of the hands in Indian housewives have been described in detail in order to focus attention on a hitherto uncommon entity. Household trauma has been incriminated as the precipitating or a triggering factor in these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Thus, while nodular clinically, there is degeneration of dermal elastic fibers histologically 27,28 . Degenerative collagenous plaques of the hands, a variant of acrokeratoelastoidosis, appears virtually identical histologically with degenerated collagen as well as elastin 32 . Most cases are asymptomatic and pose mainly cosmetic abnormality, although there may be fissuring, which may be troublesome.…”
Section: Genodermatosesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, while nodular clinically, there is degeneration of dermal elastic fibers histologically 27,28 . Degenerative collagenous plaques of the hands, a variant of acrokeratoelastoidosis, appears virtually identical histologically with degenerated collagen as well as elastin 32 . Most cases are asymptomatic and pose mainly cosmetic abnormality, although there may be fissuring, which may be troublesome.…”
Section: Genodermatosesmentioning
confidence: 99%
“…27,28 Degenerative collagenous plaques of the hands, a variant of acrokeratoelastoidosis, appears virtually identical histologically with degenerated collagen as well as elastin. 32 Most cases are asymptomatic and pose mainly cosmetic abnormality, although there may be fissuring, which may be troublesome. While most treatment efforts have been unsuccessful, erbium: yttrium-aluminium-garnet (Er:YAG) laser vaporization has shown some beneficial effect.…”
Section: Acrokeratoelastoidosismentioning
confidence: 99%
“…166,168 Men are more commonly affected than women, and the majority of but not all reported cases have been in white patients. 169 Etiology and pathogenesis. It has been suggested that chronic sun exposure and manual labor that involves chronic pressure or repeated trauma may be contributing factors, although these findings have not been universally reported among affected persons.…”
Section: Keratoelastoidosis Marginalismentioning
confidence: 99%
“…168 A lymphocytic infiltrate in the papillary dermis has also been reported. 169 Associated conditions. Keratoelastoidosis marginalis has not been associated with systemic abnormalities.…”
Section: Keratoelastoidosis Marginalismentioning
confidence: 99%
“…2,[4][5][6][7][8][9] The youngest patient reported to date is a female in her early 40s. 6 Both males and females are affected, but males are reportedly more commonly affected. Although reported in nonCaucasians, most cases of KM have been reported in faircomplexioned individuals supporting the role of actinic damage as a possible etiology.…”
Section: Discussionmentioning
confidence: 99%